Development of e-LKM for Elementary School Mathematics Learning as an Open-Ended Problem-Based Teaching Material using MiKIR Approach - Kiki Fatmawati; Ainun Mardia; Sri Lestari Handayani; Marni Zulyanty (AL-ISHLAH: Jurnal Pendidikan, 2023)
Active learning demands teaching materials that engage and motivate pupils. E-LKM is an active learning material because of this. This study develops e-LKM mathematics learning courses based on open-ended problems assisted by the LIMIT application using the MiKIR approach and describes the trial results. This e-LKM is developed using 4D models: define, design, create, and distribute. The study included University of Muhammadiyah Prof. Dr. HAMKA primary school teacher candidates. Students of UIN STS Jambi madrasah ibtidaiyah professors will test the product. Validation and practical instruments are utilised. The defined step produces the e-LKM's mathematical learning needs, including student indicators and targets. After the design stage, the mathematics learning e-LKM has a title, group name column, directions for use, lecture objectives and achievements, questions, answer columns, conclusions, and reflections. After development, the validation instrument for e-LKM was 77.33% material, 80.00% language, and 76.92% media, putting it in the correct category. Practicality instruments scored 83.76%, indicating e-LKM is practical. The distribution step will yield student and instructor opinions on e-LKM's practicality. This study suggests lecturers use LIMIT to create e-LKM and use it in learning. Research can also create an open-ended problem-based MiKIR e-LKM for additional materials.